POPULISM AND DICTATORSHIP IN THE DOMINICAN REPUBLIC: DID THE REGIME OF RAFAEL L. TRUJILLO MOLINA DEVELOP A DISCOURSE AND A SOCIAL AND ECONOMIC POLICY CLOSE TO CLASSICAL POPULISM? - Genao Núñez, Wilson (2018)
Populism is a phenomenon that historically has affected societies with very uneven levels of development, in specific historical circumstances and in very different times. It is a complex and multifaceted phenomenon that has been present in the political history of many Latin American countries. One of the historical phases of the evolution of this concept is the so-called classic populism that developed in Latin America between the post-economic crisis of 1929 and the decade of the 60s. In the Dominican Republic the Trujillo dictatorship (1930-1961) it is situated in that same historical period in which classical populism developed in Latin America. In this article, the Trujillo regime is examined from the postulates that define classical populism. Studying the main authors of classical populism and Dominican historians, the context in which it arises and the discourse and practices developed by the Trujillo regime are analyzed, from authoritarian, messianic and personalist leadership, industrialization policies via substitution of imports, the discourse on the past, the working class and the peasantry, the mobilization of the people and the handling of a nationalist discourse.